Profession and residency matter: Farmers' preferences for farmland price regulation in Germany - Johanna Jauernig; Stephan Brosig; Silke Hüttel (Journal of Agricultural Economics, 2023)
Local farmers' preferences for farmland price regulations in competitive markets have not been studied systematically. We investigate farmers' preferences in Germany, where recent price increases have driven calls for regulatory changes. The results of an online vignette experiment show that farmers prefer stricter regulation against the admission of non-local (but even more so of non-farmer) land buyers. Our analysis also shows that local farmers' preferences are motivated primarily by self-interest rather than adherence to principles. We conclude that most farmers prefer price regulations that consider their particular concerns about increasing competition in Germany.
Keywords: Q12; Q24; R38; 330; agricultural ethics; experimental evidence; farmers' preferences; farmland price regulation